Free Trade Agreements and Inequality: The Prospect for the UK Post-Brexit - Alfalah, Osama; Ali, Mohammad; Alhammadi, Abdullah (International Journal of Economics and Financial Issues, 2024)
This paper examines the potential effects of Brexit on income inequality in the United Kingdom (UK) and utilizes empirical methods to predict these effects. The study focuses on the impact of trade and Foreign Direct Investment (FDI) on income inequality, using macroeconomic data from 1971 to 2019. By employing cointegration techniques and an Error Correction Model (ECM) on annual time series data, the analysis reveals that higher levels of trade have historically reduced income inequality in the UK over the long term. Consequently, changes in trade resulting from Brexit are expected to have a negative influence on the distribution of income and wealth in the UK. On the other hand, the study finds that higher FDI has only had a short-term negative effect on income distribution in the UK.